1981
DOI: 10.1210/endo-108-5-1925
|View full text |Cite
|
Sign up to set email alerts
|

Action of Pancreatic Polypeptide on Exocrine Pancreas and on Release of Cholecystokinin and Secretin*

Abstract: We have studied the effect of exogenous porcine pancreatic polypeptide (PP; 0.8 and 2.1 microgram/kg . h, iv) on endogenously stimulated pancreatic exocrine secretion in five pancreatic-fistula dogs. Plasma levels of cholecystokinin (CCK), secretin, and PP were measured in addition to pancreatic secretion of water, bicarbonate, and protein. Intraduodenal infusions of acid and a mixture of phenylalanine and tryptophan were used to stimulate hormone release. PP caused a dose-dependent inhibition of endogenously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Lonovics et al [4] also observed an increase of PP in response to 99% pure CCK-33. which, however, was not dose dependent.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Lonovics et al [4] also observed an increase of PP in response to 99% pure CCK-33. which, however, was not dose dependent.…”
Section: Discussionmentioning
confidence: 85%
“…Our data in man confirm the findings of Regan et al [5], but are in contrast to those of Taylor et al [6], who did not observe a significant PP response to intrave nous CCK-33. The discrepancies are hard to explain, but may partly depend on differ ences in the handling of the very labile CCK peptides [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic polypeptide (PP) and somatostatin may contribute to the regulation of acinar cell function. Infusion of exogenous PP to plasma levels comparable to those observed after meal inhibits pancreatic secretion 9. This is indicative of a possible role of this peptide in the physiological control of exocrine pancreatic secretion.…”
Section: Introductionmentioning
confidence: 73%
“…Only high-capacity, low-affinity receptors of doubtful physiological relevance have been detected [19]. The action of PP is demonstrable in vivo only, not in in vitro preparations of pancreatic or biliary tissues [20,21]. Thus, it was suggested that PP must act through nerves [7].…”
mentioning
confidence: 99%